SOA-based Multiwavelength Fiber Laser Assisted by Intensity Dependent Transmission Mechanism - Sulaiman A.H.; Abdullah F.; Jamaludin M.Z.; Ismail A.; Mahdi M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Fiber lasers; Optical switches; Semiconductor optical amplifiers; Throughput; Intensity-dependent; Lasing lines; Lyot filters; Multi wavelength fiber laser; Multiwavelength; Multiwavelength spectra; Optical splitter; Transmission mechanisms; Fiber amplifiers